FUNDAMENTAL CONCEPTS AS AN INTEGRATIVE COMPONENT OF ORGANIZATION OF OPERATIONS RESEARCH FOR FUTURE BACHELOR OF INFORMATICS - Ulyana P. Kogut (Інформаційні технології і засоби навчання, 2016)
The article analyzes the role of basic concepts of operations research in teaching of future bachelor of computer science. On the basis of the analysis it was determined the possible use of modern computer mathematics systems (CMS) as a means of educational process fundamentalization. Singling out the basic concepts of operations research, their understanding through experience of research is integrable component of training, the establishment of inter-subject relationship, the formation of an integrated system of students’ knowledge and understanding of both the theoretical foundations and the ways to use the acquired knowledge in practice. Also the role of CMS in training bachelors of computer science, the directions of the pedagogical use of CMS in studying of operations research are considered.